Pengaruh Abu Vulkanik Kelud dan Pupuk Kandang terhadap Ketersediaan dan Serapan Kalium pada Jagung di Tanah Alfisol - Suntoro Suntoro; Sudadi Sudadi; Hery Widijanto; Galuh Novikah Widy Utami (Universitas Sebelas Maret, 2016)
Kelud volcanic ash has high source of minerals, which is potassium. This study aims to determine the effect and find the best composition of Kelud volcanic ash and manure to the availability and corn uptake of potassium in the Alfisols.This research is expected to provide information on the composition of volcanic ash Kelud and proper manure for agriculture. This research was conducted in the greenhouse, in the Laboratory of Ecology and Management of Crop Production, and soil chemistry laboratory of the Faculty of Agriculture, Sebelas Maret University in June 2014 - January 2015. Research using completely randomized design which consists of two factors, there are the thickness of Kelud volcanic ash which consists of four levels A0 (0 cm), A1 (2 cm), A2 (4 cm), and A3 (6 cm) and the dose of manure were P0 (0 ton/ha), P1 (2,5 ton/ha), and P2 (5 ton/ha). Each combination treatment was repeated 3 times. The data were then analyzed using the F test and continued with Duncan Multiple Range Test Test (DMRT) level of 95%. The results showed that the interaction between the two treatments were no significant different. Availability Potassium gradually decreased with an increase in the dose of volcanic ash Kelud, allegedly because of the low value of the total potassium Kelud volcanic ash. The results of measurements of plant potassium uptake increased with increasing dose Kelud volcanic ash and manure.